1984
DOI: 10.1073/pnas.81.15.4894
|View full text |Cite
|
Sign up to set email alerts
|

G gamma beta+ hereditary persistence of fetal hemoglobin: cosmid cloning and identification of a specific mutation 5' to the G gamma gene.

Abstract: Hereditary persistence of fetal hemoglobin (HPFH) is a benign condition in which the normal shutoff of fetal hemoglobin (Hb F) production fails to occur. In the G gamma beta+ type of HPFH, erythrocytes of adult heterozygotes contain approximately equal to 20% Hb F, which is almost exclusively of the G gamma-globin variety, without increased levels of gamma-globin chains from the nearby A gamma-globin gene. Unlike some forms of HPFH, no major deletions in the globin gene cluster have been found by genomic blott… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
1

Year Published

1989
1989
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 133 publications
(30 citation statements)
references
References 45 publications
(45 reference statements)
2
27
1
Order By: Relevance
“…The 0T and AT genes from chromosome A are 85% homologous over a 5-kb region (1.5 kb upstream of the gene, 1.6 kb constituting (12), and (b) it is thought that the gene conversion that occurred 1 million years ago in chromosome A has its 3' boundary in this repeat (1 1). The novel TG repeat we described in the chromosome studied has the sequence (TG)jo(CG)3(TG)9, a sequence different from all others previously described (1 1 (9,(12)(13)(14)(15), but suggests that the regulatory sequences (in the absence of such mutations) that normally determine the ratio of expression between these two genes will have to be found elsewhere.…”
Section: Introductioncontrasting
confidence: 60%
“…The 0T and AT genes from chromosome A are 85% homologous over a 5-kb region (1.5 kb upstream of the gene, 1.6 kb constituting (12), and (b) it is thought that the gene conversion that occurred 1 million years ago in chromosome A has its 3' boundary in this repeat (1 1). The novel TG repeat we described in the chromosome studied has the sequence (TG)jo(CG)3(TG)9, a sequence different from all others previously described (1 1 (9,(12)(13)(14)(15), but suggests that the regulatory sequences (in the absence of such mutations) that normally determine the ratio of expression between these two genes will have to be found elsewhere.…”
Section: Introductioncontrasting
confidence: 60%
“…The following human DNA fragments shown in Fig. 1B ␥ genes (GenBank Humhbb coordinates: 32820 to 45698) was purified from a cosmid clone containing the ␤ S -globin cluster described previously (8) and subcloned into the BamHI site of cosmid vector pWE15, which contained a modified polylinker. To construct the LCR G ␥ A ␥HPFH-2 transgene, a 12-kb BglII-HindIII genomic DNA fragment from a phage clone (B-1) containing the normal DNA overlapping the 3Ј breakpoint of HPFH-1 and HPFH-2 (42) was subcloned downstream of the 13-kb BglII genomic fragment containing the ␥-globin genes to yield a 25-kb DNA fragment whose structure is virtually identical to the structure of HPFH-2 DNA.…”
Section: Methodsmentioning
confidence: 99%
“…The first clue came from Francis Collins and colleagues who, in 1983, found that a T-to-C substitution in position 175 of the G γ promoter underlies the G γ HPFH mutation they studied [38]. The second clue came from the study of the so-called Greek A γ HPFH [39].…”
Section: Studies Of Mutantsmentioning
confidence: 99%